Teaching elementary students real-life inquiry skills - Hill, Kristy (Santa Barbara, California : Libraries Unlimited, 2019)
This book shows how to teach elementary students to locate reliable information, evaluate sources, develop their writing skills in the classroom and in the library, evaluate information, and collect it from credible sources. It explains how to incorporate writing into your makerspace, encourage curiosity through the inquiry process, help students find their voice, and support writing and prewriting for digital media. Includes lesson plans, student samples, and activities.
Part I. Real life research -- Research and the brain -- Empowering students -- When meaning drives instruction -- Writing as part of the maker movement -- Library journals -- Research methodology -- Teaching students to be critical evaluators of information -- The presentation -- Part II. Lesson plans.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on December 06, 2019).
eBooks on EBSCOhost
Keywords: Research -- Methodology -- Study and teaching (Elementary); Information literacy -- Study and teaching (Elementary); School librarian participation in curriculum planning; Inquiry-based learning; Lesson planning; Makerspaces in libraries; Writing centers; Recherche -- Méthodologie -- Étude et enseignement (Primaire); Culture de l'information -- Étude et enseignement (Primaire); Bibliothécaires scolaires -- Participation à la planification des programmes d'études.; Apprentissage basé sur l'enquête.; Préparation de cours; Laboratoires ouverts dans les bibliothèques.; Centres de communication écrite.; Library & information sciences; Information literacy -- Study and teaching (Elementary); Inquiry-based learning; Lesson planning; Makerspaces in libraries; Research -- Methodology -- Study and teaching (Elementary); School librarian participation in curriculum planning; Writing centers